Dampak Akulturasi Budaya Islam terhadap Upacara Adat Mitembeyan di Subang - Winiarti, Winiarti; Khairunnisa, Nurlaila; Safira, Putri; Verananda, Ezita; Parhan, Muhamad (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2024)
This article aims to learn more about the practice of mitembeyan traditional ceremonies and explain the impact and meaning of mitembeyan traditional ceremonies before and after Islamic acculturation. Descriptive qualitative methods were used with unstructured interview techniques to support and fulfil the research objectives. Interviews were conducted with several sources who knew about mitembeyan traditional ceremonies, and then data processing was carried out to achieve the research objectives. The findings in this research show that before acculturation with Islam, the purpose of mitembeyan was as a form of respect for Dewi Sri when starting farming, by bringing offerings and other equipment addressed to the ancestors. After mitembeyan acculturated to Islam, the goal changed to gratitude for the blessings of rice, which impacted the preparation and process of mitembeyan traditional ceremonies. Keywords: Cultural Acculturation, Islamic Acculturation, Mitembeyan